AKTIVITAS PEMASARAN DAN KEPENTINGAN NON-PENGENDALI DENGAN KINERJA TATA KELOLA SEBAGAI PEMODERASI: BUKTI DARI PASAR ASEAN - Deby Santyo Rusandy; Marhaendra Kusuma (STIE PGRI Dewantara Jombang, 2026)
The purpose of this study is to determine the effect of marketing activities on non-controlling interests' rights over corporate profits and the moderating role of governance performance in the influence of marketing activities on non-controlling interests' rights over corporate profits. The firm-year data used is 1,249 from the financial statements of companies listed on stock exchanges in five Southeast Asian countries. Moderated regression analysis was used to test the hypothesis. The results demonstrate that marketing activities have a positive effect on non-controlling interests' rights over corporate profits, and governance performance strengthens the influence of marketing activities on non-controlling interests' rights over corporate profits. This study's theoretical contribution supports agency theory, which suggests that good governance mitigates agency problems between parent owners and non-controlling interests. This study's practical contribution is a recommendation for investors with potential non-controlling interests to consider the effectiveness of marketing performance in predicting investment returns, as reflected in attributable earnings. The originality of this study lies in examining the moderating role of governance performance in the influence of marketing activities on non-controlling interests' rights over corporate profits.